2002
DOI: 10.1097/00008390-200212000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptors in human melanoma cell lines IIB-MEL-LES and IIB-MEL-IAN and in human melanoma metastases

Abstract: The presence and characteristics of androgen receptors (ARs) have been described by our group in one human melanoma cell line. We have now investigated their presence in two other human melanoma cell lines, IIB-MEL-LES and IIB-MEL-IAN, as well as in biopsies from human metastatic melanoma. Scatchard analysis revealed a single binding component for both cell lines, the apparent dissociation constant obtained being 15 nM, with a binding capacity of 280 fmol/mg total cell protein, for IIB-MEL-LES cells and 14 nM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…(4) AR positively regulates MMP9 in other cancers, including gastric, bladder, and prostate cancers (Ergun et al, 2007; Hara et al, 2008; Wang et al, 2013; Wu et al, 2010; Zhang et al, 2014). Notably, (5) melanomas express AR (Allil et al, 2008; Morvillo et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) AR positively regulates MMP9 in other cancers, including gastric, bladder, and prostate cancers (Ergun et al, 2007; Hara et al, 2008; Wang et al, 2013; Wu et al, 2010; Zhang et al, 2014). Notably, (5) melanomas express AR (Allil et al, 2008; Morvillo et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…In the years since this study, other studies have confirmed that females have a significant survival advantage compared to males (38%), fewer and delayed metastases, longer delay before relapse, and higher cure rates than males, strongly suggesting a biological basis for the observed gender bias (Bidoli et al, 2012; de Vries et al, 2007; Fisher and Geller, 2013; Gamba et al, 2013; Geller et al, 2002; Joosse et al, 2012; Joosse et al, 2011; Schwartz et al, 2002; Swetter et al, 2009). Differences in expression or activity of sex-hormone receptors, including the estrogen receptor or AR, have long been considered a plausible explanation for the melanoma gender bias (de Giorgi et al, 2011; Morvillo et al, 2002). Recent studies favor a deleterious role for AR and androgens in melanoma, as (1) the female advantage persists even in post-menopausal women, suggesting against an estrogen-related advantage (de Vries et al, 2008; Joosse et al, 2011; Micheli et al, 2009) and (2) there is an increased risk of melanoma following prostate cancer, and vice-versa, suggesting an AR-based connection between the two cancers (Li et al, 2013b; Spanogle et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This trait results in sex differences in survival and progression across the whole spectrum of the disease, from early to late stages. 30 Further research is needed to confirm or exclude any of these hypothetical biologic explanations. 25 However ER-␤ expression declines after menopause 25 and therefore the ER-␤ hypothesis dictates that in postmenopausal women, the advantage over men should decline or even disappear.…”
Section: Figmentioning
confidence: 99%
“…However, a subsequent study showed that metastatic melanoma tissue specimens were positive for testosterone receptors, which, when activated, stimulate proliferation. These receptors also appeared to be activated by estrogen, and tamoxifen blunted the proliferative effect of estrogen on these receptors [Morvillo et al, 2002]. Importantly, the use of oral contraceptives (OCP) or hormone replacement therapy (HRT) did not appear to increase the risk of melanoma or worsen the prognosis of melanoma [Durvasula et al, 2002;MacKie, 1999;Pfahlberg et al, 1997].…”
Section: Hormones and Melanomamentioning
confidence: 99%